Wear and corrosion performance of laser-clad low-carbon high-molybdenum Stellite alloys. (November 2018) - Yao, Jianhua; Ding, Yinping; Liu, Rong; Zhang, Qunli; Wang, Liang
Highlights: Modified low-C high-Mo Stellite 22 & Stellite 728 were prepared via laser cladding. Mo-rich intermetallic compound Co3 Mo is precipitated in these alloys. Co3 Mo can increase hardness and wear resistance of the Stellite alloy. Stellite 22 and Stellite 728 exhibit similar corrosion resistance to Stellite 21. Oxide film was retained better on Stellite 21 than on Stellite 22 and Stellite 728. Abstract: Low-carbon Stellite alloys such as Stellite 21 exhibit good high-temperature and corrosion properties but need improved wear resistance in some applications. In this research, two low-carbon Stellite alloys with highly increased molybdenum content are produced via laser cladding. The microstructures of the laser cladding hardfacings are studied using scanning electron microscopy (SEM) with an energy dispersive X-ray (EDS) spectroscopy, and X-ray diffraction. The wear resistance of the hardfacings is evaluated using a pin-on-disc tribometer. The corrosion performance of the hardfacings is investigated under electrochemical tests in 3.5 wt.% sodium chloride (NaCl) solution and in Green Death solution. The experimental results show that the presence of Mo-rich intermetallic compounds enhances the wear resistance of the alloy hardfacings significantly. Since Stellite alloys are all able to form protective oxide films due to high chromium content against corrosion of the substrates, the bonding strength and repair ability of the oxide films dominate the corrosion resistance of the hardfacings in the corrosive environments. Stellite 21 hardfacing is also studied under the same testing conditions for comparison.